Enfoque de la identidad gastronómica en las fiestas del Yamor y San Juan en la ciudad de Otavalo - Echeverria Mateus, David Patricio (2024)
The San Juan and Yamor festivals in Otavalo, located in the Imbabura Geopark, Ecuador, play a fundamental role in local gastronomy and culinary culture. These celebrations in Otavalo are intrinsically related to the local gastronomy and culinary culture of this city, highlighted by its recipes such as Yamor chicha, champús, fritada, roasted guinea pig, various types of empanadas, and products like grains, especially corn. The general objective of this study is to research and promote the gastronomic and festive culture of the city of Otavalo by investigating and documenting the importance of the Yamor and San Juan festivals, as well as compiling recipes to preserve and disseminate the traditional dishes linked to these celebrations. To achieve these objectives, a basic mixed-methods research approach was employed. Quantitative data were collected through surveys of the local community, represented by 166 people, while qualitative data were obtained through five semi-structured interviews with gastronomy experts and community members. The results are evidenced in a compilation of twelve representative Otavalo dishes presented in a recipe book titled “Festival Flavors: Recipes from Yamor and San Juan in Otavalo.” It is concluded that the San Juan and Yamor festivities are crucial for the intergenerational transmission of Otavalo's culinary culture.